Combination of CAD/CAM and Augmented Reality in Free Fibula Bone Harvest. Issue 11 (November 2019) - Battaglia, Salvatore; Badiali, Giovanni; Cercenelli, Laura; Bortolani, Barbara; Marcelli, Emanuela; Cipriani, Riccardo; Contedini, Federico; Marchetti, Claudio; Tarsitano, Achille
Abstract : Summary: The CAD/CAM technology for mandibular reconstruction has improved the results in terms of outcomes in restoring mandibular complex defects. Augmented reality (AR) represents an evolution of the navigation-assisted surgery. This technology merges the images of the virtual planning with the anatomy of the patient, representing in this way an enhanced scene for the surgeon's eye. AR can also display in a single scene additional information for the surgeon. Despite of classical navigation, this scenario can be obtained with marker-less registration method, without using reference points or fiducial markers. This technologic evolution together with the large use in our experience of CAD/CAM protocol for mandibular reconstruction we developed this feasibility study to evaluate the possibility of using a marker-less image registration system. Moreover, we tried to evaluate the overlaying of the virtual planning and its reproducibility using AR. We performed a case series of 3 consecutive patients who underwent mandibular reconstruction using AR-assisted fibular free flap harvesting applying our digital workflow. Once launched, the mobile app installed on our tablet, the registration is performed according to a shape recognition system of the leg of the patient, rendering in real time a superimposition of the anatomy of the bony, vascular, and skin of the patient and also the surgical planning of the reconstruction. AR-assisted fibular free flap harvesting was performed. We believe that AR can be a prospective improving technology for mandibular complex reconstruction. Abstract : Supplemental Digital Content is available in the text.